Current Methods, Common Practices, and Perspectives in Tracking and Monitoring Bioinoculants in Soil - Manfredini, Andrea; Malusà, Eligio; Costa, Corrado; Pallottino, Federico; Mocali, Stefano; Pinzari, Flavia; Canfora, Loredana (Frontiers in Microbiology, 2021)
Microorganisms promised to lead the bio-based revolution for a more sustainable agriculture. Beneficial microorganisms could be a valid alternative to the use of chemical fertilisers or pesticides. However, the increasing use of microbial inoculants is also raising several questions about their efficacy and their effects on the autochthonous soil microorganisms. There are two major issues on the application of bioinoculants to soil: i) their detection in soil, and the analysis of their persistence and fate; ii) the monitoring of the impact of the introduced bioinoculant on native soil microbial communities. This review explores the strategies and methods that can be applied to the detection of microbial inoculants and to soil monitoring. The discussion includes a comprehensive critical assessment of the available tools, based on morpho-phenological, molecular and microscopic analyses. The prospects for future development of protocols for regulatory or commercial purposes are also discussed, underlining the need for a multi-method (polyphasic) approach to ensure the necessary level of discrimination required to track and monitor bioinoculants in soil.